Networking event between IPSis and faculties through MiKEPPS platform - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
Institute Postgraduate Studies (IPSis) co-hosted by the Postgraduate office, UiTM Kedah successfully organized the “Mesyuarat IPSis Bersama Ketua/Koordinator Pusat Pengajian Siswazah” (MiKEPPS) on 27th-29th January 2023 at Swiss Avenue Hotel, Sungai Petani, Kedah Darul Aman. The meeting was attended by 39 Head and Coordinators of Postgraduate Centers from Colleges, Faculties, Academic Centre and UiTM Branch campuses. This meeting constituted a good opportunity to foster the networking and sharing of knowledge among Heads and Coordinators of the Postgraduate Center in improving governance, accountability and effective development delivery and results to improve UiTM postgraduate operational efficiency.